Lead exposure: occupational and environmental health effect - อันติมานนท์, อรพันธ์; จงสู่วิวัฒนวงศ์, วีระศักดิ์ (Disease Control Journal, 2014)
Lead is a soft, gray, heavy metal widely distributed in the earth's crust. The common sources of human exposure can be divided into two main types, namely purely natural sources and sources involving anthropogenic or industrial activity, specific industries and work activities have been associated with occupational lead exposure, including metal smelting, battery manufacturing and recycling, construction, automotive manufacture and repair, ceramics manufacture, wooden-boat building and repair, and work involving ammunition and guns. Lead from such sources can contaminate the surrounding environments including soil, dust, air, surface water, drinking water and food. Soil contains lead from many sources and this can remain for centuries, as lead has a low mobility in soil. Soil lead concentrations have been found to peak at the location of industrial sources and decrease with increasing distance from the point sources. Contributions to the lead content of household dust derive from soil, airborne emissions and take-home lead by lead-exposed workers. Ingestion of house dust and soil which contain small amounts of lead is one source of lead intake in humans. Environmental air lead levels have fallen worldwide, as leaded petrol has been phased out. The toxic effects of lead can be manifested in multiple organs. The major targets of lead toxicity are the peripheral and central nervous system. It is particularly harmful to the developing brain and nervous system of foetuses and young children. Moreover, lead may produce anemia both by inhibiting heme synthesis and by accelerating erythrocyte destruction. It also induces interstitial nephritis, tubular damage, hyperuricaemia and an increase in systolic blood pressure or hypertension. Lead-exposed workers are the first group that requires to be monitored to limit exposure. Household members of workers are also at risk for lead poisoning if lead is carried home on a worker's body, clothes or shoes. Children may have elevated blood lead concentrations as a result of accessing potential sources such as lead paint, bare soil and household dust. Hazard surveillance and health surveillance should be recommended to control lead exposure for all risk groups.